VIRTUAL REALITY BASED ANDROID APPLICATION FOR SPECIAL CHILDREN - Bhatti, Zeeshan; Shabbir, Naila; Arshad, Maryam; Shaikh, Midhat (Journal of Information Systems and Digital Technologies, 2021)
Dyscalculia is a hidden neurological disorder in which a child feels difficulty while learning mathematics. Several Virtual reality based applications for cognitive learning for a special group of users have been developed and effectively used to learn complex concepts of various subjects. In our proposed virtual reality android based application we try to combat the issues of dyscalculia children to learn and understand basic of place value of digits and basic mathematical operations in an effective and immersive interactive environment of Virtual reality based class room.